Pancreatic Metastasis from Colon Carcinoma Nine Years after a Hemicolectomy Managed by Distal Pancreatectomy. A Review of the Literature Regarding the Role and Outcome of Pancreatic Resection for Colorectal Metastasis - Machado, Norman Oneil; Chopra, Pradeep J; Al Hamdani, Aisha (JOP. Journal of the Pancreas, 2010)
Context Pancreatic metastasis from colorectal malignancy is rare and accounts for less than 2% of all pancreatic metastases. A case of colonic metastasis to the pancreas is reported and the literature is reviewed to assess the role and outcome of pancreatic resection for metastatic tumors from colorectal malignancy. Case report A 58-year-old female underwent an emergency left hemicolectomy for an obstructing descending colon growth. The lesion was reported to be adenocarcinoma, Dukes C, with involvement of the serosa and 3 lymph nodes. A postoperative staging CT scan showed no other metastases and she received 6 cycles of FOLFOX chemotherapy (folinic acid, 5-flurouracil and oxaliplatin). Nine years after the colectomy during a routine follow-up, there was a sudden rise in her CEA levels. A CT scan revealed a 6.8x4.8 cm mixed consistency lesion in the tail of the pancreas which, on fine needle aspiration cytology, was confirmed to be adenocarcinoma. She underwent a distal pancreatectomy, and histopathology of the resected specimen confirmed a metastatic tumor from colon cancer. She then received 5 cycles of adjuvant chemotherapy. She was symptom free for nine months and subsequently succumbed to recurrent disease. Conclusion Pancreatic metastasis from colorectal malignancy is rare. These patients could be asymptomatic in 17% of cases. The time-interval between the diagnosis of colorectal cancer and the detection of pancreatic metastasis varies widely but is approximately 24 months. The median survival time for post-pancreatic resection is 16 months. Pancreatic resection appears to offer good palliation until recurrence of the disease occurs and the possibility of long term cure is rare. Image: Cut section of the distal pancreatectomy specimen revealing the cystic necrotic center of the metastatic tumor from cancer of the descending colon.